PEMBAGIAN HARTA WARISAN SEBELUM PEWARIS MENINGGAL DI DESA WANGKALKEPUH GUDO JOMBANG DALAM KACAMATA HUKUM ISLAM DAN SADD AL-DZARI’AT - Shiddiq, Muhammad Ilham; Muhammad Muhammad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The distribution of inheritance is something that someone will definitely experience when they have a family. Where the property rights of someone who has died are given and who will take care of the property is the reason for the need to divide the inheritance. For this reason, Islamic law protects the rights and obligations of both the testator and the heirs. However, the different situations of different people and different times bring new problems that must be faced. One of the problems faced is what happened in the village of Wangkalkepuh, Gudo sub-district, Jombang district. In this village, there have been several problems where a person distributes his inheritance before he dies. This becomes a problem because depending on whether the distribution is considered as inheritance or as a grant it will have different legal effects. The reason why this method of distribution is used is also an important consideration for the legal status of the distribution of the property. The focus of this research is to answer this issue, namely the question of how the people of Wangkalkepuh village distribute the inheritance before the testator dies and what is the reason they do it and how Islamic law responds to this action. This research is a qualitative field research with sociological approach method. While the data collection technique is using interviews, observation and documentation methode. And the data analysis technique uses a methode of looking at cases and fact, describing the data obtained and interpreting the data based on the theory used as a reference. The results of the study found that the division of property carried out by the people of Wangkalkepuh Village is a valid grant contract and is separate from the distribution of inheritance which will still be carried out after the testator dies. In some families, it was also found that the calculation of the grant property was part of the inheritance when the testator died. The reason why the people of Wangkalkepuh Village use this method is to avoid conflict. However, this reason is not enough to be able to make the Sadd al-Dzari'at rule to be applied. So that the law if the division of inheritance is still carried out cannot be forbidden.